Rapid onset of altered mental status with progressive autonomic instability and hypoventilation in a 2-year-old male - Ramin Nazari; Carlos A Carmona-Jr (The Turkish Journal of Pediatrics)
Anti N-methyl-D-aspartate receptor (NMDAR) encephalitis should be suspected in children who report with acute behavioral change, seizures, and non-specific movement disorders. While historically associated with adolescent females with ovarian teratoma, anti-NMDAR encephalitis has now been described in the pediatric population of both sexes. These patients display the neurological and psychiatric manifestations similar to females but lack a tumor. We report a two-year-old previously healthy young male who presented with alteration in speech, seizures, and extra pyramidal movement disorders. He was diagnosed with anti-NMDAR encephalitis with positive cerebrospinal fluid (CSF) serology for anti-NMDAR antibodies. In this case report, we describe the clinical presentation, course of illness, investigation, and management of our patient. We conclude by emphasizing three observations and insights from our case compared to what is mentioned in the literature.